GLUCOSENS study protocol: a continuous glucose monitoring system compared to fingerstick glucose monitoring in surgical wards – a two-centre before-after clinical trial - Karoline Schousboe; Helen Schultz; Marian Christin Petersen; Kasper Baasch Nielsen; Line Abrahamsen; Torill Donslund Nielsen; Ulla Linding Joergensen; Tine Lumbye Thomsen (BMJ Open)
Introduction Effective glucose control in surgical patients at risk of hyperglycaemia and hypoglycaemia is crucial, as these conditions can lead to surgical site infections, prolonged hospital stays and death. Fingerstick glucose monitoring (FSGM), the standard measurement of glucose, can be painful for patients and time-consuming for nursing staff, especially with hourly monitoring around surgery. Continuous glucose monitoring systems (CGMS) offer a less invasive alternative with better glucose regulation in outpatients.The GLUCOSENS study compares the effects of CGMS and FSGM on point-of-care measurements and time-in-range (3.9–10.0 mmol/l) glucose levels (primary outcome), patient satisfaction and experience and nursing staff workload and experience in surgical wards. Furthermore, it evaluates CGMS accuracy during perioperative periods and medical imaging.Methods and analysis This Danish two-centre study will be conducted at the general surgical wards of Odense and Zealand University Hospital and will involve 305 patients over 18 months. The study is divided into three periods: first, a standard care period with point-of-care FSGM (110 patients); second, an intervention period with point-of-care CGMS (110 patients); third, another standard care period with point-of-care FSGM combined with a blinded sensor for comparing continuous glucose data from this period with continuous glucose data from the intervention period (85 patients). Furthermore, the study will include 24 nursing staff.Data will be collected through medical file reviews on glucose levels, patient satisfaction questionnaires, a patient field study, an observation study of the nursing staff’s workload and qualitative interviews of nursing staff.Ethics and dissemination The study is registered with the Records of Processing Activities in the Region of Southern Denmark for research and quality projects (ID number: 23/36734) and has been approved by the Regional Scientific Ethical Committee in Southern Denmark (ID number: S-20240041). The results will be published in international peer-reviewed journals.Trail registration number ClinicalTrials.gov Registry (NCT06473480)